2016
DOI: 10.5001/omj.2016.05
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Dietary Intakes of Amino Acids and Bone Mineral Density Among Individuals with Spinal Cord Injury

Abstract: We found that high protein intake led to a lower BMD of lumbar vertebrae in patients with SCI after controlling for confounders including demographic and injury-related characteristics and calcium intake. No relationship between higher amino acids intake and BMD of the femur and hip was detected. Intake of alanine, arginine, and aspartic acid were not related to BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
0
11
1
Order By: Relevance
“…This pattern could represent a new metabolic pathway between OP and CAC. Previously, higher leucine and valine dietary intakes have been associated with low BMD in spinal cord injury subjects, 29 in contrast with our results. Thus, nutrition may explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…This pattern could represent a new metabolic pathway between OP and CAC. Previously, higher leucine and valine dietary intakes have been associated with low BMD in spinal cord injury subjects, 29 in contrast with our results. Thus, nutrition may explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…There is very limited knowledge about the roles of the amino acid threonine and the two amino acid derivatives, stachydrine and formylkynurenine, in bone metabolism. A human study among individuals with spinal cord injury reported that a higher intake of threonine was related to a lower BMD of lumbar vertebrae [ 36 ]. However, we found that the serum threonine level was positively associated with BMD among young women.…”
Section: Discussionmentioning
confidence: 99%
“…The essential amino acid methionine has become a compound of interest as a growing number of studies are revealing its molecular role in physiological remodeling. Previous studies have established a causal relationship between high methionine levels and complications such as arteriosclerosis, osteoporosis, growth retardation, uremia, vascular remodeling and hepatoxicity (Yang et al 2015; Sabour et al 2016; Harper et al 1970; Mori et al 2000; Chaturvedi et al 2016; Gomez et al 2009). Moreover, studies have also identified high methionine as a risk factor for developing cognitive disorders (Miller, 2003; Zhuo et al 2010).…”
Section: Introductionmentioning
confidence: 99%